Cloning of a novel neuronally expressed orphan G-protein-coupled receptor which is up-regulated by erythropoietin, interacts with microtubule-associated protein 1b and colocalizes with the 5-hydroxytryptamine 2a receptor - Maurer, Martin H.; Grünewald, Sylvia; Gaßler, Nikolaus; Roßner, Moritz; Propst, Friedrich; Würz, Rebecca; Weber, Daniela; Kuner, Thomas; Kuschinsky, Wolfgang; Schneider, Armin (Journal of neurochemistry, 2004)
G-protein-coupled receptors (GPCRs) are the largest group of cell surface molecules involved in signal transduction and are receptors for a wide variety of stimuli ranging from light, calcium and odourants to biogenic amines and peptides. It is assumed that systematic genomic data-mining has identified the overwhelming majority of all remaining GPCRs in the genome. Here we report the cloning of a novel orphan GPCR which was identified in a search for erythropoietin-induced genes in the brain as a strongly up-regulated gene. This unknown gene coded for a protein which had a seven-transmembrane topology and key features typical of GPCRs of the A family but a low overall identity to all known GPCRs. The protein, coded ee3, has an unusually high evolutionary conservation and is expressed in neurons in diverse areas of the CNS with relation to integrative functions or motor tasks. A yeast two-hybrid screen for interacting proteins revealed binding to the microtubule-associated protein (MAP) 1b. Coupling to MAP1a has been described for another cognate GPCR, the 5-hydroxytryptamine (5HT) 2a receptor. Surprisingly, we found complete colocalization of ee3 and the 5HT2a receptor. The interaction with MAP1b proved to be critical for the stability or folding of ee3 as in mice lacking MAP1b the ee3 protein was undetectable by immunohistochemistry, although messenger RNA levels remained unchanged. We propose that ee3 is a highly interesting new orphan GPCR with potential connections to erythropoietin and 5HT2a receptor signalling.